Identification of the Pyroptosis-Related Gene Signature and Risk Score Model for Colon Adenocarcinoma - Luo, Bixian; Lin, Jianwei; Cai, Wei; Wang, Mingliang (Frontiers in Genetics, 2021)
The prognosis of advanced colon adenocarcinoma (COAD) remains poor. However, existing methods are still difficult to assess patient prognosis. Pyroptosis, as a lytic and inflammatory process of programmed cell death caused by gasdermin protein, is involved in the development and progression of various tumors. Moreover, there are no related studies using pyroptosis-related genes to construct a model to predict the prognosis of COAD patients. Thus, in this study, bioinformatics methods were used to analyze the data of COAD patients download from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases to construct risk model for the patient prognosis. TCGA database was used as the training set, and GSE39582 downloaded from GEO was used as the validation set. 24 pyroptosis-related genes shown significantly different expression between normal and tumor tissues in COAD, and seven genes (CASP4, CASP5, CASP9, IL6, NOD1, PJVK, PRKACA), screened by univariate and LASSO cox regression analysis were used to construct risk model. The receiver operating characteristic (ROC) curves and Kaplan-Meier (K-M curves) showed that model based on pyroptosis-related genes can be used to predict the prognosis of COAD and validated by external cohort well. Then, the clinicopathological factors were combined with risk score to establish a nomogram with C-index of 0.774. In addition, tissue validation results also showed that CASP4, CASP5, PRKACA and NOD1 were differentially expressed between tumor and normal tissues from COAD patients. In conclusion, the risk model based on pyroptosis-related gene can be used to assess the prognosis of COAD patients well and related genes may become the potential targets for treatment.